1972
DOI: 10.1021/je60055a017
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of lithium fluoride in water

Abstract: The solubility of lithium fluoride in water increases only slightly with temperature in the range measured, going from 0.132% at 23.7°C to 0.150% at 81.8°C. The solubility product of lithium fluoride determined at 30°C in the presence of the common ions agreed within 0.2 X 10"3 of the 2.8 X 10~3 value calculated from flame photometric lithium measurements made at the same temperature on pure lithium fluoride solutions. Solubility results verify those determined gravimetrically over the range of 0-35°C by Payne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 1 publication
1
29
0
Order By: Relevance
“…While in PC, LiF is not very soluble (s = 0.14 g L −1 ), DMC presents an intermediate value of 0.57 g L −1 . For comparison purposes, we have determined in the same manner the solubility of LiF in water (s = 1.11 g L −1 ) and this value is within close range to the data obtained by Stubblefield and Bach [5] (1.33 g L −1 ). Large differences in solubility are noted between the alkylcarbonates in spite of their structural similarities.…”
Section: Lif Solubilitiessupporting
confidence: 81%
See 1 more Smart Citation
“…While in PC, LiF is not very soluble (s = 0.14 g L −1 ), DMC presents an intermediate value of 0.57 g L −1 . For comparison purposes, we have determined in the same manner the solubility of LiF in water (s = 1.11 g L −1 ) and this value is within close range to the data obtained by Stubblefield and Bach [5] (1.33 g L −1 ). Large differences in solubility are noted between the alkylcarbonates in spite of their structural similarities.…”
Section: Lif Solubilitiessupporting
confidence: 81%
“…At the exception of LiF in water where the solubility has been determined by gravimetry [4] and by ion selective electrode method [4,5], few data are available concerning the solubility of lithium fluoride in dipolar aprotic solvents versus temperature. In particular, to our knowledge, no studies concerning the solubility of LiF in alkylcarbonates and lactones have been yet reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, as LiF is only slightly soluble in water (1.33 g L -1 at 291 K), [26] and is considered virtually insoluble in organic solvents, [27] the solubility in organic electrolytes has not been consistently reported (although it is known to be higher in DMSO, 0.37 g L -1 , [28] compared to e.g. PC or DEC; see Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The samples turned to be sensitive to the wet vehicle during the polishing procedure. LiF is slightly soluble in water 46 , while LiYF 4 is insoluble 47 . This can be a convenient tool to generate etched microstructured LiYF 4 surfaces.…”
Section: Selective Etching Of the Minority Lif Phase: Microporous Liymentioning
confidence: 99%